PENGARUH ATRIBUT PRODUK TERHADAP KEPUTUSAN PEMBELIAN MELALUI MINAT BELI SEBAGAI VARIABEL MEDIASI - Marshella Riyanto; Yunita Ismail Masjud (President University, 2017)
The study was made based on Honda Beat motorcycle sales decline in sales data from CV Lestari Motor Jonggol. Therefore, the purpose of the study is to determine the effect of product attributes on purchasing decisions through buying interest as a mediation variable. The research method is quantitative research with descriptive-explanatory study type using product attribute as exogenous variable, buying interest as mediation variable, and purchase decision as endogenous variable with 17 manifest variables. The object of the research is the user of Honda Beat motorcycle who made a purchase at CV Lestari Motor Jonggol. Sampling using non-probability sampling method with accidental sampling technique. The study was conducted by distributing questionnaires containing closed questions to 100 respondents. Data analysis used descriptive analysis such as percentage analysis and index analysis, and statistical analysis in the form of Structural Equation Modeling analysis with Partial Least Square and mediation effect analysis. Based on the result of research known that product attribute influence purchasing decision through buying interest as mediation variable that acts as partial mediator, so can conclude that there is influence of product attribute to purchasing decision through buying interest as mediating variable to consumer of Honda Beat motorcycle in CV Lestari Motor Jonggol